Predicting pathological response to chemoradiotherapy for rectal cancer: a systematic review. Issue 5 (4th May 2021) - Fischer, Jesse; Eglinton, Tim W; Richards, Simon JG; Frizelle, Frank A
ABSTRACT: Introduction : Pathological complete response (pCR) rates of approximately 20% following neoadjuvant long-course chemoradiotherapy for rectal cancer have given rise to non-operative or watch-and-wait (W&W) management. To improve outcomes there has been significant research into predictors of response. The goal is to optimize selection for W&W, avoid chemoradiotherapy in those who won't benefit and improve treatment to maximize the clinical complete response (cCR) rate and the number of patients who can be considered for W&W. Areas covered : A systematic review of articles published 2008–2018 and indexed in PubMed, Embase or Medline was performed to identify predictors of pathological response (including pCR and recognized tumor regression grades) to fluoropyrimidine-based chemoradiotherapy in patients who underwent total mesorectal excision for rectal cancer. Evidence for clinical, biomarker and radiological predictors is discussed as well as potential future directions. Expert opinion : Our current ability to predict the response to chemoradiotherapy for rectal cancer is very limited. cCR of 40% has been achieved with total neoadjuvant therapy. If neoadjuvant treatment for rectal cancer continues to improve it is possible that the treatment for rectal cancer may eventually parallel that of anal squamous cell carcinoma, with surgery reserved for the minority of patients who don't respond to chemoradiotherapy.